Factors influencing internet banking adoption: a study on employees in UiTM Cawangan Melaka Kampus Bandaraya Melaka / Nur Afinie Mohd Husaini - Mohd Husaini, Nur Afinie (Faculty of Business and Management, 2018)
This research aims to examine the factors influencing of internet banking adoption on employees in UiTM Cawangan Melaka Kampus Bandaraya Melaka. Two objectives were proposed in this study. First, this study aimed to examine the relationship between in dependent variables (self-efficacy, convenience, security, trust and social influence) and dependent variable (Internet banking adoption). Second, this study intends to identify the most influence factor on Internet banking adoption. A total of 118 usable questionnaires was keyed in and analysed by using SPSS software version 20. Furthermore, this study also used probability, simple random sampling to select the right element from the population sampling. The data collected were used to create descriptive, correlation and regression analysis. Regression results revealed that there are significant relationships between all independent variables (self-efficacy, convenience, security, trust and social influence) and dependant variable (Internet banking adoption). From overall analysis, it shows that trust gave the strongest influence towards Internet banking adoption. Last but not least, this finding is useful to banking industry so that they can enhance and improve their services and also useful for customers and future researcher as they might contribute more on Internet banking adoption.